Reengineering anthrax toxin protective antigen for improved receptor-specific protein delivery - Lukas Becker; Wouter P. R. Verdurmen; Andreas Plückthun (BMC Biology, 2020)
Abstract Background To increase the size of the druggable proteome, it would be highly desirable to devise efficient methods to translocate designed binding proteins to the cytosol, as they could specifically target flat and hydrophobic protein-protein interfaces. If this could be done in a manner dependent on a cell surface receptor, two layers of specificity would be obtained: one for the cell type and the other for the cytosolic target. Bacterial protein toxins have naturally evolved such systems. Anthrax toxin consists of a pore-forming translocation unit (protective antigen (PA)) and a separate protein payload. When engineering PA to ablate binding to its own receptor and instead binding to a receptor of choice, by fusing a designed ankyrin repeat protein (DARPin), uptake in new cell types can be achieved. Results Prepore-to-pore conversion of redirected PA already occurs at the cell surface, limiting the amount of PA that can be administered and thus limiting the amount of delivered payload. We hypothesized that the reason is a lack of a stabilizing interaction with wild-type PA receptor. We have now reengineered PA to incorporate the binding domain of the anthrax receptor CMG2, followed by a DARPin, binding to the receptor of choice. This construct is indeed stabilized, undergoes prepore-to-pore conversion only in late endosomes, can be administered to much higher concentrations without showing toxicity, and consequently delivers much higher amounts of payload to the cytosol. Conclusion We believe that this reengineered system is an important step forward to addressing efficient cell-specific delivery of proteins to the cytosol.